A current view on Tau protein phosphorylation in Alzheimer's disease. (August 2021) - Wegmann, Susanne; Biernat, Jacek; Mandelkow, Eckhard
Abstract: The functions of the neuronal microtubule-associated protein Tau in the central nervous system are regulated by manifold posttranslational modifications at more than 50 sites. Tau in healthy neurons carries multiple phosphate groups, mostly in its microtubule assembly domain. Elevated phosphorylation and aggregation of Tau are widely considered pathological hallmarks in Alzheimer's disease (AD) and other tauopathies, triggering the quest for Tau posttranslational modifications in the disease context. However, the phosphorylation patterns of physiological and pathological Tau are surprisingly similar and heterogenous, making it difficult to identify specific modifications as therapeutic targets and biomarkers for AD. We present a concise summary of - and view on - important previous and recent advances in Tau phosphorylation analysis in the context of AD. Highlights: Phosphorylation of insoluble Tau commonly defines targets for current AD therapies. High phosphorylation does not necessarily lead to Tau aggregation. CSF Tau fragments are well characterized but lack functional and mechanistic data.